MAIN FEATURES OF REDUCTION OF VOWELS IN ENGLISH (Academicia Globe: Inderscience Research, 2023)
This article discusses specific peculiarities of vowel reduction in English pronunciation. Different types of vowel reduction will be analyzed in this paper. Besides that, certain ways of teaching the pronunciation of words with reduced vowels will be suggested in this research.